2013
DOI: 10.1186/1471-2164-14-403
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling by microarray and marker analysis of the short cotton (Gossypium hirsutum L.) fiber mutant Ligon lintless-1 (Li 1 )

Abstract: BackgroundCotton fiber length is very important to the quality of textiles. Understanding the genetics and physiology of cotton fiber elongation can provide valuable tools to the cotton industry by targeting genes or other molecules responsible for fiber elongation. Ligon Lintless-1 (Li1) is a monogenic mutant in Upland cotton (Gossypium hirsutum) which exhibits an early cessation of fiber elongation resulting in very short fibers (< 6 mm) at maturity. This presents an excellent model system for studying the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 85 publications
2
69
0
Order By: Relevance
“…The plants and populations used in this study were all described previously (Gilbert et al 2013). Briefly, near isogenic lines (NIL) of Li 1 mutant and its wild-type G. hirsutum cv.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plants and populations used in this study were all described previously (Gilbert et al 2013). Briefly, near isogenic lines (NIL) of Li 1 mutant and its wild-type G. hirsutum cv.…”
Section: Plant Materialsmentioning
confidence: 99%
“…While wild-type cotton fiber cells of 1 3 G. hirsutum cv. DP5690 impressively elongate up to 30 mm in 4 weeks of development with fastest elongation around 8 days post anthesis (DPA), the Li 1 fiber cells only extend about 3 mm when fully mature (Gilbert et al 2013). The single dominant gene that confers this qualitative short fiber phenotype has previously been mapped to a region of chromosome 22 that has also been repeatedly identified in studies of quantitative cotton fiber traits, including quantitative trail loci (QTLs) for fiber length, fiber uniformity and yield of seed cotton Fang et al 2014;Jiang et al 1998;Karaca et al 2002;Rong et al 2005;Yu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gravimetric methods that examine changes in fiber composition (i.e., pectin, cellulose and lignin content) can consume significant amounts of sample, which complicates their use in fiber development studies [7,8]. More recent efforts have used Fourier transform-infrared (FT-IR) techniques to explore cell walls and their development in cotton fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Many genes were recognized to be altered in the Li 1 mutant line for early termination of fiber elongation. Several additional studies have also identified factors that affect Li-associated genes at the downstream position [43].…”
Section: Mapping For Fiber-related Traits In Cottonmentioning
confidence: 99%